Laparoscopic Cystectomy of Huge Ovarian Cyst in Nulliparous Woman - Thakur, Amarnath; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema Kumari; Shrestha, Ranjana; Bhattachan, Kabin; Poudel, Rekha; Bajracharya, Nishma; Giri, Kanti Prabha; Tiwari, Kenusha Devi (Nepal Journal of Obstetrics and Gynaecology, 2018)
Mucinous cystadenoma arises from the totipotent surface epithelium of the ovary. Its association with Brenner tumor suggests its origin as mucinous metaplasia of the epithelioid cells. The chance of malignancy is 5–10 percent. Patients usually present with abruptly increasing abdominal mass. Cystectomy is the management of choice in these cases. It was managed by laparoscopy.